Negative electrode for lithium secondary battery and method for producing same
By combining carbon material and silicon material in the negative electrode of the lithium-ion secondary battery and oriented the carbon-based negative electrode active layer with a magnetic field, the problem of difficult to take into account the charge and discharge performance and life characteristics of the negative electrode in the prior art is solved, and battery performance with high energy density and long life is achieved.
Patent Information
- Application Number
- JP2024556534
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-15
- Filing Date
- 2023-11-27
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-11-27
AI Technical Summary
The prior art is difficult to improve the charging and discharging performance of the negative electrode of the lithium-ion secondary battery while maintaining the high energy density and long life characteristics.
Using a negative electrode containing carbon material and silicon material, by controlling the crystal structure characteristics of the carbon-based negative electrode living body, the negative electrode living layer is oriented with a magnetic field to ensure the efficient Alignment of the negative electrode living body during the charging and discharging process.
The high charge and discharge capability and long life characteristics of the negative electrode during long-term charge and discharge process are achieved, ensuring the high energy density and stable performance of lithium-ion secondary batteries.
Smart Images

Figure 2025511597000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same, which has excellent charge / discharge characteristics and life characteristics.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0169280 dated December 7, 2022 and Korean Patent Application No. 10-2023-0076626 dated June 15, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference. [Background technology]
[0003] In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- and large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices. This has led to a wide range of research into batteries that can meet a variety of needs. In particular, research into lithium secondary batteries that have high energy density and excellent life and cycle characteristics as power sources for medium- and large-sized devices has been actively conducted.
[0004] Lithium secondary batteries are power generating elements that can be charged and discharged and are made up of a laminated structure of a positive electrode / separator / negative electrode. When charging a lithium secondary battery, a lithium desorption reaction occurs in which lithium contained in the positive electrode active material is oxidized and released at the positive electrode inside the battery, and a lithium insertion reaction occurs in which lithium is reduced at the negative electrode and inserted into the negative electrode active material. In general, in lithium secondary batteries, the desorption reaction at the positive electrode active material is faster than the insertion reaction at the negative electrode active material, so the charging speed and other performance are mainly determined by the negative electrode.
[0005] In reality, carbon materials containing graphite are widely used as the negative electrode active material of the negative electrode. For example, graphite has a layered structure in which layers formed of carbon atoms in a network structure are stacked. As a result, in the graphite, lithium ions penetrate into the edge surface (surface where the layers overlap) of the carbon layer during charging and diffuse between the layers, and the diffused lithium ions are desorbed during discharging and released from the edge surface of the carbon layer. In addition, since the electrical resistivity of the carbon layer in the plane direction of the graphite is lower than that in the stacking direction of the carbon layer, a detouring electron conduction path is formed along the plane direction of the carbon layer.
[0006] In this regard, a technique has been proposed for magnetically orienting the graphite contained in the negative electrode in order to improve the charging performance of the negative electrode in lithium secondary batteries using carbon materials such as graphite. Specifically, the (0,0,2) crystal plane of the graphite is oriented in a magnetic field during the formation of the negative electrode so that it is almost horizontal to the negative electrode current collector, and then fixed. In this case, the edge face of the carbon layer of the graphite in the manufactured negative electrode faces the positive electrode active layer, so that the insertion and desorption of lithium ions is smoothly performed, and at the same time, the electron conduction path is shortened, and the electronic conductivity of the negative electrode can be improved, thereby improving the charging performance of the battery.
[0007] On the other hand, the average potential when carbon materials such as graphite release lithium is about 0.2 V (Li / Li + (reference), and the discharge potential shows a relatively flat phase. Therefore, a negative electrode containing graphite as a negative electrode active material has the advantage that the voltage of a secondary battery is high and constant. The electric capacity per unit mass of such carbon materials such as graphite is theoretically 372 mAh / g. However, since the capacity of the carbon materials is improved close to the theoretical capacity, it is difficult to further increase the capacity, and there is a limit in that it is difficult to increase the energy density of the manufactured negative electrode.
[0008] Therefore, various negative electrode active materials have been researched to improve the capacity and energy density of lithium secondary batteries. For example, silicon materials such as silicon (Si) and silicon oxide (SiO2) are known to be capable of reversibly absorbing and releasing a large amount of lithium by a compound formation reaction with lithium, and many studies have been conducted recently. Silicon materials have a theoretical maximum capacity of about 4020 mAh / g (9800 mAh / cc, specific gravity 2.23). This is a very large value compared to graphite-based materials, which means that silicon is useful as a high energy density and / or high capacity negative electrode material compared to graphite-based materials. However, silicon materials show a large volume change (up to 300%) during charging and discharging. Therefore, a negative electrode containing both a carbon material and a silicon material as a negative electrode active material has a high energy density of the electrode, but has a limitation in that the adhesive strength between the negative electrode active layer and the negative electrode current collector is significantly reduced, resulting in low durability. In particular, when the (0,0,2) crystal plane of the graphite is oriented approximately parallel to the negative electrode current collector, the edge plane alignment of the carbon layer of the carbon material is significantly damaged and / or lost due to the large volume change of the silicon material, which limits the charging and life characteristics of the negative electrode when the negative electrode is charged and discharged for a long period of time.
[0009] Therefore, there is a strong need for a negative electrode technology for lithium secondary batteries that contains both a carbon material and a silicon material as negative electrode active materials and that not only has excellent charge / discharge capacity and energy density but also exhibits high charge characteristics and life characteristics even during long-term charge / discharge. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Korean Patent Publication No. 10-2020-0047287 Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a negative electrode for a lithium secondary battery which contains both a carbon material and a silicon material as negative electrode active materials, has excellent charge / discharge capacity and energy density, and exhibits high charge characteristics and life characteristics even during long-term charge / discharge, and a lithium secondary battery containing the same. [Means for solving the problem]
[0012] To solve the above-mentioned problems, In one embodiment, the present invention comprises: A negative electrode current collector, and a negative electrode active layer provided on at least one surface of the negative electrode current collector and including a carbon-based negative electrode active material and a silicon-based negative electrode active material; The negative electrode active layer is The degree of alignment (OI) of the carbon-based negative electrode active material after activation a ) is less than or equal to 3, Provided is a negative electrode for a secondary battery that satisfies the following formula 1:
[0013] [Formula 1] 0.5≦[OI a ] / [OI r ]<1.0
[0014] In the above formula 1, OI r represents the degree of alignment (OI) of the carbon-based negative electrode active material measured before activation, OI a represents the degree of alignment (OI) of the carbon-based negative electrode active material measured after activation, The degree of alignment (OI) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy analysis of the negative electrode active layer.
[0015] In this case, the carbon-based negative electrode active material may have an average particle size (Dc) of 5 μm to 50 μm, the silicon-based negative electrode active material may have an average particle size (Ds) of 0.5 μm to 10 μm, and the ratio of the average particle sizes of the carbon-based negative electrode active material and the silicon-based negative electrode active material (Dc / Ds) may be 1 to 10.
[0016] The silicon-based negative electrode active material may be included in an amount of 1 wt % to 20 wt % based on the total weight of the negative electrode active material.
[0017] The carbon-based negative electrode active material may include at least one of natural graphite and artificial graphite.
[0018] The silicon-based negative electrode active material is silicon (Si), silicon carbide (SiC), and silicon oxide (SiO q , where 0.8≦q≦2.5) may be included.
[0019] The negative electrode active layer has a thickness of 150 mg / 25 cm 2 ~300mg / 25cm 2 and the average thickness may be 10 μm to 100 μm.
[0020] In one embodiment, the present invention further comprises: applying a negative electrode slurry containing a carbon-based negative electrode active material and a silicon-based negative electrode active material to at least one surface of a negative electrode current collector; applying a magnetic field to the applied negative electrode slurry; drying and rolling the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; The negative electrode active layer is The degree of alignment (OI) of the carbon-based negative electrode active material after activation a ) is less than or equal to 3, The present invention provides a method for producing a negative electrode for a lithium secondary battery according to the present invention, which satisfies the following formula 1:
[0021] [Formula 1] 0.5≦[OI a ] / [OI r ]<1.0
[0022] In the above formula 1, OI r represents the degree of alignment (OI) of the carbon-based negative electrode active material measured before activation, OI arepresents the degree of alignment (OI) of the carbon-based negative electrode active material measured after activation, The degree of alignment (OI) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy analysis of the negative electrode active layer.
[0023] Here, the step of applying the magnetic field may be performed with a magnetic field strength of 3,000 G to 9,000 G for 1 second to 30 seconds.
[0024] The rolling may be carried out at a temperature of 20° C. to 35° C. and a pressure of 50 MPa to 200 MPa.
[0025] In one embodiment, the present invention further comprises: There is provided a lithium secondary battery including an electrode assembly including a positive electrode, the negative electrode according to the present invention, and a separator disposed between the positive electrode and the negative electrode.
[0026] In this case, the positive electrode may include a positive electrode active material layer provided on at least one surface of a positive electrode current collector and including one or more positive electrode active materials selected from lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2:
[0027] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2
[0028] [Chemical formula 2] LiM 2 p Mn 1-p O4
[0029] In the above Chemical Formula 1 and Chemical Formula 2, M 1is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつ、y+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is in the range of 0.05≦p≦1.0.
[0030] Further, in one embodiment, the present invention provides activating a lithium secondary battery including an electrode assembly including a positive electrode, the negative electrode according to the present invention described above, and a separator disposed between the positive electrode and the negative electrode; The negative electrode active layer of the negative electrode is characterized by the degree of alignment (OI) of the carbon-based negative electrode active material after activation. a ) is 3 or less, and satisfies the following formula 1:
[0031] [Formula 1] 0.5≦[OI a ] / [OI r ]<1.0
[0032] In the above formula 1, OI r represents the degree of alignment (OI) of the carbon-based negative electrode active material measured before activation, OI a represents the degree of alignment (OI) of the carbon-based negative electrode active material measured after activation, The degree of alignment (OI) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy analysis of the negative electrode active layer.
[0033] At this time, the activation step can be performed by charging and discharging at a rate of 0.01C to 0.9C two or more times. Effect of the Invention
[0034] The negative electrode for a lithium secondary battery according to the present invention contains both a carbon-based negative electrode active material and a silicon-based negative electrode active material as negative electrode active materials, and exhibits excellent characteristics in charge / discharge capacity and energy density. In addition, the negative electrode has an alignment degree (OI) of the carbon-based negative electrode active material after activation. a ) is the degree of alignment (OI) of the carbon-based negative electrode active material before activation. r ) is realized in a predetermined range lower than the above, it has an advantage that the secondary battery shows high charging characteristics and life characteristics during long-term charging and discharging. [Brief description of the drawings]
[0035] [Figure 1] 1 shows an image illustrating the alignment of ab-axis crystal planes of graphite depending on whether or not a magnetic field is applied to a negative electrode slurry during the formation of a negative electrode active layer, where (a) shows a case where a magnetic field is not applied and the graphite crystal planes are not aligned, and (b) shows a case where a magnetic field is applied and the graphite crystal planes are aligned. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] Since the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be described in detail.
[0037] However, this is not intended to limit the invention to any particular embodiment, but it should be understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.
[0038] In the present invention, terms such as "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and may be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0039] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.
[0040] In the present invention, "containing as a main component" may mean containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more), or 95% by weight or more (or 95% by volume or more) of a defined component based on the total weight (or total volume). For example, "containing graphite as a main component as a negative electrode active material" may mean containing 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more of graphite based on the total weight of the negative electrode active material, and in some cases, it may mean that the entire negative electrode active material is made of graphite and contains 100% by weight of graphite.
[0041] In addition, in this specification, "the carbon-based negative electrode active material is oriented" or "the carbon-based negative electrode active material is aligned" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material constituting the negative electrode active material particles is arranged to have a specific inclination based on the surface of the negative electrode current collector. This may be different from the carbon-based negative electrode active material particles themselves being arranged to have a specific direction inside the negative electrode active layer.
[0042] In addition, "high orientation of the carbon-based negative electrode active material" may mean that a specific crystal plane (e.g., the ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer has a high frequency of having a certain inclination with respect to the surface of the negative electrode current collector. In some cases, it may mean that the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, more than 45°, specifically 60° or more) with respect to the surface of the negative electrode current collector.
[0043] In addition, "high degree of alignment of carbon-based negative electrode active material" may mean that the "degree of alignment (OI)" referred to in this specification is large, and a specific crystal plane (e.g., ab-axis crystal plane of graphite) showing a two-dimensional planar structure of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a low angle (e.g., less than 45°) with respect to the surface of the negative electrode current collector. Conversely, "low degree of alignment of carbon-based negative electrode active material" may mean that the "degree of alignment (OI)" is small, and the crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle (e.g., an angle close to vertical, 45° or more, specifically 60° or more) with respect to the surface of the negative electrode current collector.
[0044] Furthermore, in this specification, the term "crystal plane of a carbon-based negative electrode active material" refers to a plane in which the atoms of the carbon-based negative electrode active material form the outer shape of a crystal. In the present invention, this may mean a crystal plane including a flat surface of the carbon-based negative electrode active material, or a crystal plane including the a-axis / b-axis / ab-axis of the carbon-based negative electrode active material crystal.
[0045] In addition, in this specification, "average particle size (D 50 ) refers to the particle size at which the cumulative value in the particle size distribution of the particles is 50%, and is also called the median diameter.
[0046] The present invention will now be described in more detail.
[0047] <Negative electrodes for lithium secondary batteries>
[0048] In one embodiment, the present invention comprises: a negative electrode current collector; and a negative electrode active layer provided on at least one surface of the negative electrode current collector, the negative electrode active layer including a carbon-based negative electrode active material and a silicon-based negative electrode active material; The negative electrode active layer is The degree of alignment (OI) of the carbon-based negative electrode active material after activation a ) is less than or equal to 3, Provided is a negative electrode for a secondary battery that satisfies the following formula 1:
[0049] [Formula 1] 0.5≦[OI a ] / [OI r ]<1.0
[0050] In the above formula 1, OI r represents the degree of alignment (OI) of the carbon-based negative electrode active material measured before activation, OI a represents the degree of alignment (OI) of the carbon-based negative electrode active material measured after activation, The degree of alignment (OI) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy analysis of the negative electrode active layer.
[0051] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode current collector and a negative electrode active layer on at least one surface of the negative electrode current collector. The negative electrode active layer is a layer that realizes electrical activity of the negative electrode and includes a negative electrode active material that realizes an electrochemical oxidation-reduction reaction during charging and discharging of the battery.
[0052] Here, the present invention includes, as the negative electrode active material contained in the negative electrode active layer, a carbon-based negative electrode active material containing carbon atoms as a main component, and a silicon-based negative electrode active material containing silicon atoms as a main component.
[0053] The carbon-based negative electrode active material may have a layered structure in which layers formed of carbon atoms in a network structure are stacked. In the carbon-based negative electrode active material having such a structure, lithium ions penetrate into the edge surface (surface where layers overlap) of the carbon layer during charging and diffuse between the layers, and the diffused lithium ions are desorbed during discharging and released from the edge surface of the carbon layer. In the carbon-based negative electrode active material, the electrical resistivity in the plane direction of the carbon layer is lower than that in the stacking direction of the carbon layer, so that a bypass electron conduction path is formed along the plane direction of the carbon layer.
[0054] Therefore, the present invention is characterized by excellent charging performance by controlling the crystal structure characteristics of the carbon-based negative electrode active material contained in the negative electrode active layer to shorten the ion path of lithium ions and reduce the resistance in the plane direction of the carbon layer.
[0055] As an example, the carbon-based negative electrode active material contained in the negative electrode active layer has an alignment degree (OI) that indicates the degree of inclination of the ab-axis crystal plane with respect to the negative electrode current collector. a ) may be 3.0 or less. Here, the degree of alignment (OI) is an alignment value calculated after activation of the secondary battery, and may be calculated by the following Equation 3:
[0056] [Formula 3] OI=I 004 / I 110
[0057] In Equation 3, I 004 represents the area of the peak showing the (0,0,4) crystal plane of the carbon-based negative electrode active material in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer, I 110 represents the area of the peak showing the (1,1,0) crystal plane of the carbon-based negative electrode active material in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer.
[0058] The degree of alignment (OI) of the carbon-based negative electrode active material can be an index showing the degree to which the ab-axis crystal plane of the carbon-based negative electrode active material is oriented in a certain direction, specifically, with respect to the surface of the negative electrode current collector, when measured by X-ray diffraction (XRD). Specifically, the negative electrode active layer shows 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°, which are peaks for the carbon-based negative electrode active material graphite when measured by X-ray diffraction. These represent the (0,0,2) plane, (1,0,0) plane, (1,0,1)R plane, (1,0,1)H plane, (0,0,4) plane, and (1,1,0) plane of graphite. Here, the peak appearing at 2θ=43.4±0.2° may be due to an overlap of the (1,0,1)R plane of the carbon-based negative electrode active material and the (1,1,1) plane of the current collector, for example, copper (Cu).
[0059] The degree of alignment (OI) of the carbon-based negative electrode active material can be measured based on the ratio of the area obtained by integrating the intensity of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the intensity of the peak at 2θ=77.5±0.2° representing the (1,1,0) plane.
[0060] The peak at 2θ=54.7±0.2° is a peak indicating a crystal plane of the carbon-based negative electrode active material that has a tilt with respect to the negative electrode current collector, so the closer the OI value is to 0, the closer the tilt with respect to the negative electrode current collector surface is to 90°, and the larger the OI value is, the closer the tilt with respect to the negative electrode current collector surface is to 0° or 180°. That is, the negative electrode active layer according to the present invention may be aligned such that the carbon-based negative electrode active material has an angle of 60° or more, 70° or more, 70 to 90°, 80 to 90°, 65 to 85°, or 70 to 85° with respect to the negative electrode current collector. As a result, the negative electrode active layer may have a lower OI of the carbon-based negative electrode active material compared to a case where the carbon-based negative electrode active material is aligned at a low angle of less than 60°.
[0061] For example, the negative electrode active layer has an alignment degree (OI) of the carbon-based negative electrode active material. a) may be 3.0 or less, specifically, 0.1 to 3.0, 0.5 to 2.9, 1.0 to 2.9, 1.5 to 2.9, 1.8 to 2.9, 1.7 to 2.7, 1.8 to 2.3, 2.2 to 2.8, or 1.9 to 2.5. Here, the degree of alignment (OI) indicates the degree of alignment of the ab-axis crystal plane of the carbon-based negative electrode active material, and does not indicate the degree to which the carbon-based negative electrode active material particles are rotated and aligned within the active layer.
[0062] The negative electrode active layer includes a silicon-based negative electrode active material. The silicon-based negative electrode active material has a theoretical maximum capacity of about 4020 mAh / g and is useful as a high energy density and / or high capacity negative electrode material. However, the silicon-based negative electrode active material exhibits a large volume change (up to 300%) during charging and discharging, which may reduce the durability of the electrode. In particular, when the ab-axis crystal plane of the carbon-based negative electrode active material is oriented so as to be nearly horizontal to the negative electrode current collector in order to improve the charging performance of the negative electrode active layer, the silicon-based negative electrode active material may significantly damage and / or lose the alignment during charging and discharging. Such damage to the orientation of the carbon-based negative electrode active material causes a problem of significantly reducing the charging characteristics and life characteristics of the negative electrode during long-term charging and discharging of the secondary battery.
[0063] However, the negative electrode according to the present invention has a low degree of alignment (OI) of the carbon-based negative electrode active material after activation. a ) is the degree of alignment (OI) of the carbon-based negative electrode active material before activation. r ) to overcome the problems associated with silicon-based negative electrode active materials.
[0064] As an example, the negative electrode is characterized in that the degree of alignment (OI) of the carbon-based negative electrode active material after activation is a ) is the degree of alignment (OI r ) and may satisfy the following formula 1 at 0.5 or more and less than 1:
[0065] [Formula 1] 0.5≦[OI a ] / [OI r ]<1.0
[0066] In the above formula 1, OI r represents the degree of alignment (OI) of the carbon-based negative electrode active material measured before activation, OI a represents the degree of alignment (OI) of the carbon-based negative electrode active material measured after activation, The degree of alignment (OI) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy analysis of the negative electrode active layer.
[0067] The formula 1 indicates that the ab-axis crystal plane of the activated carbon-based negative active material is aligned at a higher angle to the negative current collector, which means that the orientation of the carbon-based negative active material in the negative active layer is improved by the activation of the secondary battery.
[0068] Activation is a step of electrically activating a lithium secondary battery, and a path for lithium ions to move in the negative electrode active layer during charging and discharging can be secured. The lithium ions are inserted (intercalated) between the layers of the carbon-based negative electrode active material and between the crystals of the silicon-based negative electrode active material during charging, and are deintercalated (deintercalated) during discharging. Therefore, activation can be said to be a process of securing such insertion and deintercalation paths for lithium ions. Here, as shown in FIG. 1, the carbon-based negative electrode active material may have a characteristic that the ab-axis crystal plane is oriented at a high inclination close to perpendicular to the negative electrode current collector, and the path for lithium ions generated from the positive electrode active layer to move is short. However, when the secondary battery is charged and discharged for a long period of time, the volume of the carbon-based negative electrode active material may continuously change due to the insertion and deintercalation of lithium ions. In addition, the silicon-based negative electrode active material located between the carbon-based negative electrode active materials expands in volume due to the insertion of lithium ions during charging. Such contraction and expansion of the negative electrode active material may reduce the inclination of the crystal plane of the carbon-based negative electrode active material with respect to the negative electrode current collector.
[0069] Thus, the negative electrode of the present invention can secure a lithium ion migration path while minimizing damage and / or loss of the inclination of the ab-axis crystal plane of the carbon-based negative active material contained in the negative active layer with respect to the negative current collector during activation. The lithium ion migration path secured in this manner is strong and is less deformed even when the secondary battery is charged and discharged for a long period of time, so that the possibility of damage and / or loss of the alignment of the carbon-based negative active material in the negative active layer is significantly reduced.
[0070] The negative electrode of the present invention has an alignment degree (OI) of the carbon-based negative electrode active material after activation. a ) is the degree of alignment (OI r ) and the above formula 1 is embodied as 0.5 or more and less than 1.0 (i.e., 0.5≦[OI a ] / [OI r Specifically, the negative electrode satisfies the above formula 1 of 0.5 or more and 0.95 or less (i.e., 0.5≦[OI a ] / [OI r ]≦0.95), and more specifically, the above formula 1 can be satisfied within a range of 0.6 to 0.95 (i.e., 0.6≦[OI a ] / [OI r ]≦0.95), 0.65~0.75 (i.e., 0.65≦[OI a ] / [OI r ]≦0.75), 0.85~0.95 (i.e., 0.85≦[OI a ] / [OI r ]≦0.95), 0.70~0.93 (i.e., 0.70≦[OI a ] / [OI r ]≦0.93), or 0.72 to 0.90 (i.e., 0.72≦[OI a ] / [OI r ]≦0.90). As a result, the negative electrode according to the present invention exhibits excellent effects on the charge characteristics and life characteristics during long-term charge and discharge of the secondary battery.
[0071] In addition, in order to firmly secure a migration path of lithium ions in the negative electrode active layer during activation of the secondary battery, the present invention can control the types of carbon-based negative electrode active material and silicon-based negative electrode active material constituting the negative electrode active layer, and the morphology, particle size, content, etc. in the negative electrode active layer to satisfy predetermined conditions.
[0072] First, the carbon-based negative electrode active material may include graphite. The graphite may include at least one of natural graphite and artificial graphite. For example, the carbon-based negative electrode active material may include natural graphite or artificial graphite alone, or may include a mixture of natural graphite and artificial graphite in some cases. In this case, the mixture ratio of natural graphite to artificial graphite may be 5-50:50-95 or 10-40:60-90 by weight. By including natural graphite and artificial graphite in the above mixture ratio, the carbon-based negative electrode active material may realize high orientation of the carbon-based negative electrode active material on the surface of the negative electrode current collector while strengthening the adhesion between the negative electrode current collector and the negative electrode active layer.
[0073] As an example, the carbon-based negative electrode active material may contain natural graphite and artificial graphite in a weight ratio of 10-30:70-90.
[0074] As another example, natural graphite and artificial graphite may be contained in a weight ratio of 25-45:55-75.
[0075] As another example, the carbon-based negative electrode active material may include artificial graphite alone.
[0076] The carbon-based negative electrode active material is preferably a spherical graphite granule formed by the aggregation of a plurality of flake graphite. Examples of flake graphite include natural graphite, artificial graphite, mesophase calcined carbon (bulk mesophase) made from tar and pitch, graphitized cokes (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc. In particular, a graphite granule assembled from a plurality of natural graphites having high crystallinity is preferable. Also, one graphite granule may be formed by the aggregation of 2 to 100 flake graphite particles, preferably 3 to 20 flake graphite particles.
[0077] Such a carbon-based negative electrode active material may have a spherical particle shape. In this case, the sphericity of the graphite particles may be 0.75 or more, for example, 0.75 to 1.0, 0.75 to 0.95, 0.8 to 0.95, or 0.90 to 0.99. Here, the "sphericity" may mean the ratio of the shortest diameter (minor axis) to the longest diameter (major axis) among any diameters passing through the center of the particle. When the sphericity is 1, it means that the particle shape is spherical. The sphericity may be measured using a particle shape analyzer, or may be determined by measuring the particle shape using a scanning electron microscope (SEM) or an energy dispersive spectrometer, and then analyzing the measurement results.
[0078] The present invention can realize high electrical conductivity of the negative electrode active layer by realizing a nearly spherical shape of the carbon-based negative electrode active material. Therefore, a negative electrode including a spherical carbon-based negative electrode active material can improve the capacity of a secondary battery and can increase the specific surface area per unit weight of the negative electrode active material, thereby improving the adhesive strength between the negative electrode active layer and the current collector.
[0079] Examples of the silicon-based negative electrode active material include silicon (Si), silicon carbide (SiC), silicon monoxide (SiO), and silicon dioxide (SiO2), which may be contained alone or in combination in the negative electrode active layer. When silicon monoxide (SiO) and silicon dioxide (SiO2) are uniformly mixed or composited as the silicon-based negative electrode active material and contained in the negative electrode active layer, they are called silicon oxide (SiO q , where 0.8≦q≦2.5).
[0080] In addition, the silicon-based negative electrode active material may be doped or alloyed with Li, Mg, Al, Ca, Ti, etc. In addition, when the silicon-based negative electrode active material contains oxygen (O), the surface of the silicon-based negative electrode active material may be treated with a carbon coating layer or the like to suppress volume expansion during charging and improve the electrical conductivity of the negative electrode active material.
[0081] In addition, the carbon-based negative electrode active material and the silicon-based negative electrode active material contained in the negative electrode active layer, i.e., the total negative electrode active material, may be included in an amount of 85 parts by weight or more, specifically, 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the total weight of the negative electrode active layer.
[0082] In addition, the silicon-based negative electrode active material may be included in an amount of 1 wt% to 20 wt% based on the total weight of the negative electrode active material, specifically, 5 wt% to 20 wt%, 1 wt% to 9 wt%, 5 wt% to 15 wt%, 3 wt% to 7 wt%, 11 wt% to 19 wt%, 13 wt% to 17 wt%, 15 wt% to 20 wt%, 8 wt% to 14 wt%, or 5 wt% to 9 wt%. The present invention can improve the charge capacity per unit mass while reducing the lithium consumption and irreversible capacity loss during activation of the secondary battery by controlling the ratio of the total content of the negative electrode active material contained in the negative electrode active layer and the ratio of the content of the silicon-based negative electrode active material contained in the total negative electrode active material within the above range. In addition, the volume change of the negative electrode active layer during charging and discharging of the secondary battery can be minimized to improve the structural stability of the negative electrode active layer, thereby improving the life characteristics of the secondary battery.
[0083] In addition, the carbon-based negative electrode active material and the silicon-based negative electrode active material contained in the negative electrode active layer have a predetermined average particle size (D 50 Specifically, the carbon-based negative electrode active material may have an average particle size (D 50 , Dc) is 5 μm to 50 μm, and the average particle size (D 50 , Ds) may be 0.5 μm to 10 μm, and the ratio of the average particle size of the carbon-based negative electrode active material to the silicon-based negative electrode active material (Dc / Ds) may be 1-10.
[0084] Specifically, the carbon-based negative electrode active material has an average particle size (D 50, Dc), and may be selectively applied within the above range according to the average thickness of the negative electrode active layer. For example, the carbon-based negative electrode active material may have an average particle size (D 50 ) can be shown. The spherical carbon-based negative electrode active material may be advantageous in that the particle size is made smaller to maximize the degree of disorder in the expansion direction of each particle so as to prevent the particles from expanding due to charging of lithium ions. However, if the particle size of the carbon-based negative electrode active material is less than 5.0 μm, a large amount of binder is required due to the increase in the number of particles per unit volume, and the sphericity and sphericity yield may be reduced. On the other hand, if the maximum particle size exceeds 50 μm, the expansion rate of the negative electrode active material during charging and discharging of the secondary battery increases significantly, and the adhesion between the particles of the negative electrode active material and the adhesion between the negative electrode active material particles and the current collector decreases due to repeated charging and discharging, and the cycle characteristics may be significantly reduced.
[0085] In addition, the silicon-based negative electrode active material has an average particle size (D 50 , Ds), specifically, an average particle size (D 50 ) can be shown.
[0086] When the silicon-based negative electrode active material has a minimum particle size of less than 0.5 μm, it is difficult to uniformly disperse the negative electrode active layer, and as the secondary battery is charged and discharged, the oxidation-reduction reaction is non-uniformly induced between the regions where the silicon-based negative electrode active material is aggregated and the regions where it is not aggregated, which may accelerate the deterioration of the negative electrode active layer. In addition, when the silicon-based negative electrode active material has a maximum particle size of more than 10 μm, the volume expansion of the silicon-based negative electrode active material during charging increases significantly, and the inclination of the ab-axis crystal plane of the carbon-based negative electrode active material decreases (i.e., the degree of alignment (OI) increases), which causes a problem that the cycle characteristics decrease significantly as the secondary battery is repeatedly charged and discharged.
[0087] Furthermore, the ratio of average particle sizes of the carbon-based negative electrode active material to the silicon-based negative electrode active material (Dc / Ds) may be 1 to 10, specifically 2 to 7, 2 to 5, 3 to 7, 4 to 8, 5 to 10, 6 to 9, or 1.5 to 4.7.
[0088] The present invention can induce a structure in which the silicon-based negative electrode active material is filled into voids formed by a plurality of carbon-based negative electrode active materials by making the ratio (Dc / Ds) of the average particle diameters of the carbon-based negative electrode active material and the silicon-based negative electrode active material satisfy the above range. At this time, the voids act as a buffer to buffer the volume expansion of the silicon-based negative electrode active material during charging and discharging of the secondary battery, thereby minimizing the volume expansion of the negative electrode active layer. In addition, if the ratio (Dc / Ds) of the average particle diameters exceeds the upper limit of the above range, there is a problem in that the deterioration of the negative electrode active layer during charging and discharging of the secondary battery is accelerated, resulting in a shortened lifespan.
[0089] Meanwhile, the average thickness of the negative electrode active layer may be 10 μm to 100 μm, specifically, 20 μm to 90 μm, 50 μm to 90 μm, 80 μm to 90 μm, 40 μm to 70 μm, or 55 μm to 68 μm.
[0090] The average loading amount of the negative electrode active layer is 150 mg / 25 cm 2 ~300mg / 25cm 2 Specifically, 180 mg / 25 cm 2 ~280mg / 25cm 2, 180mg / 25cm 2 ~250mg / 25cm 2 , 200mg / 25cm 2 ~250mg / 25cm 2 , or 200 mg / 25 cm 2 ~220mg / 25cm 2 It could be.
[0091] In the present invention, by adjusting the average thickness and / or average loading amount of the negative electrode active layer within the above range, the crystallinity of the negative electrode active material contained in the negative electrode active layer can be easily controlled, and the energy density of the negative electrode can be further increased.
[0092] In addition, the negative electrode active layer according to the present invention may further selectively contain, in addition to the negative electrode active material as the main component, a conductive material, a binder, other additives, and the like, as necessary.
[0093] The conductive material may include, but is not limited to, one or more of carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, and the like.
[0094] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., alone or in combination, as a conductive material.
[0095] At this time, the content of the conductive material may be 0.1 parts by weight to 10 parts by weight, specifically 0.1 parts by weight to 8 parts by weight, 0.1 parts by weight to 5 parts by weight, 0.1 parts by weight to 3 parts by weight, 2 parts by weight to 6 parts by weight, or 0.5 parts by weight to 2 parts by weight. By controlling the content of the conductive material within the above range, the present invention can prevent the resistance of the negative electrode from increasing due to a low content of the conductive material, resulting in a decrease in the charging capacity. In addition, the problem of the content of the negative electrode active material decreasing due to an excessive amount of the conductive material, resulting in a decrease in the charging capacity, or the problem of the rapid charging characteristics decreasing due to an increase in the loading amount of the negative electrode active layer can be prevented.
[0096] In addition, the binder is a component that aids in bonding between the negative electrode active material and the conductive material and the current collector, and may be suitably applied within a range that does not deteriorate the electrical properties of the electrode. Specifically, the binder may include any one or more selected from the group consisting of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), and fluororubber.
[0097] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the binder contained in the negative electrode active layer within the above range, the present invention can prevent a decrease in adhesive strength of the active layer due to a low content of the binder, or a decrease in electrical properties of the electrode due to an excessive amount of the binder.
[0098] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, nickel, titanium, calcined carbon, etc., and in the case of copper or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. The average thickness of the negative electrode current collector may be suitably 1 μm to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.
[0099] <Method of manufacturing negative electrode for lithium secondary battery>
[0100] In one embodiment, the present invention further comprises: applying a negative electrode slurry containing a carbon-based negative electrode active material and a silicon-based negative electrode active material to at least one surface of a negative electrode current collector; applying a magnetic field to the applied negative electrode slurry; drying and rolling the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; The negative electrode active layer is The degree of alignment (OI) of the carbon-based negative electrode active material after activation a ) is less than or equal to 3, The present invention provides a method for producing a negative electrode for a lithium secondary battery that satisfies the following formula 1:
[0101] [Formula 1] 0.5≦[OI a ] / [OI r ]<1.0
[0102] In the above formula 1, OI r represents the degree of alignment (OI) of the carbon-based negative electrode active material measured before activation, OI a represents the degree of alignment (OI) of the carbon-based negative electrode active material measured after activation, The degree of alignment (OI) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy analysis of the negative electrode active layer.
[0103] The method for producing the negative electrode according to the present invention means a method for producing the above-mentioned negative electrode according to the present invention. The method for producing the negative electrode may be performed by coating a negative electrode slurry on a negative electrode current collector, applying a magnetic field to the surface of the coated negative electrode slurry, and then drying and rolling the negative electrode slurry to form a negative electrode active layer.
[0104] Here, the step of applying the negative electrode slurry is a step of discharging and coating the negative electrode slurry containing a carbon-based negative electrode active material onto the surface of a moving negative electrode current collector. The step may be applied without any particular limitation as long as it is a method commonly applied in the art, but preferably, a die coating method may be used. The die coating method may be performed using a slot die having a shim for controlling the discharging conditions of the negative electrode slurry. In this case, the loading amount and coating thickness of the negative electrode slurry applied onto the negative electrode current collector may be easily controlled by controlling the shape of the shim.
[0105] The negative electrode slurry contains a carbon-based negative electrode active material and a silicon-based negative electrode active material as main components, and may further contain, as necessary, a conductive material, a binder, other additives, etc. In this case, the carbon-based negative electrode active material and the silicon-based negative electrode active material, the conductive material, the binder, other additives, etc. have the same configuration as the configuration of the negative electrode for the lithium secondary battery described above, so a detailed description will be omitted.
[0106] In addition, the step of applying a magnetic field to the negative electrode slurry may be a process of controlling the crystal characteristics of the negative electrode active material contained in the negative electrode slurry and reducing the degree of disorder of the carbon-based negative electrode active material contained in the negative electrode slurry. Specifically, this step may align the ab-axis crystal plane of the carbon-based negative electrode active material contained in each negative electrode slurry to have a high angle with respect to the negative electrode current collector by applying a magnetic field to the surface of the negative electrode slurry coated on the negative electrode current collector.
[0107] In this case, the magnetic field may be applied by magnet units disposed above and below the negative electrode current collector moving with the negative electrode slurry coated on its surface, and the polarities of the magnet units disposed above and below the negative electrode current collector may be different from each other.
[0108] In addition, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the negative electrode slurry may be adjusted by the strength and application time of the applied magnetic field, and thus the step of applying the magnetic field may be performed under predetermined magnetic field strength and application time conditions.
[0109] Specifically, the step of applying a magnetic field may apply a magnetic field of 10,000 G (Gauss) or less, specifically, a magnetic field may be applied with an intensity of 3,000G to 9,000G, 3,000G to 8,500G, 3,500G to 8,500G, 4,000G to 8,200G, 3,600G to 4,500G, 4,500G to 6,500G, 5,000G to 7,000G, 6,000G to 8,500G, 7,000G to 8,500G, 6,000G to 6,500G, or 4,000G to 5,000G.
[0110] Furthermore, the step of applying the magnetic field may be carried out for 1 to 30 seconds, specifically for 1 to 20 seconds, 1 to 15 seconds, 1 to 10 seconds, 5 to 20 seconds, 10 to 20 seconds, 11 to 19 seconds, 14 to 18 seconds, 4 to 9 seconds, or 6 to 11 seconds.
[0111] As one example, in the step of applying a magnetic field, a magnetic field of 4,700±50 G may be applied to the negative electrode slurry for 3 to 8 seconds.
[0112] As another example, in the step of applying a magnetic field, a magnetic field of 4,700±50 G may be applied to the negative electrode slurry for 12 to 17 seconds.
[0113] Furthermore, the step of applying the magnetic field may be performed by magnet parts introduced on the upper and lower parts of the applied negative electrode slurry, and may be performed in a state where the size of the magnet parts is adjusted to be larger than the size of the negative electrode slurry. For example, the magnet parts may have a length ratio of 105% to 200% based on the width direction length of the negative electrode slurry, and more specifically, may have a length ratio of 110% to 180%, 110% to 160%, 110% to 140%, 110% to 130%, 130% to 150%, or 105% to 120% based on the width direction length of the negative electrode slurry. In this case, since the magnetic field applied to the negative electrode slurry is uniformly applied to the entire surface of the negative electrode slurry, the degree of alignment (OI) of the carbon-based negative electrode active material may be uniformly realized.
[0114] In addition, the step of forming the negative electrode active layer may refer to a process of drying the negative electrode slurry to which a magnetic field is applied, and then firmly fixing the oriented carbon-based negative electrode active material. Therefore, the step of forming the negative electrode active layer may be applied without any particular limitation as long as it is a method capable of maintaining the degree of alignment (OI) of the carbon-based negative electrode active material contained in the negative electrode active layer.
[0115] For example, the drying can be performed by applying thermal energy to the negative electrode slurry using a hot air dryer, a vacuum oven, or the like.
[0116] The rolling is a step of increasing the density of the negative electrode active layer by applying pressure to the dried negative electrode slurry using a roll press, etc. Here, the rolling may be performed under conditions that do not increase the degree of alignment (OI) of the carbon-based negative electrode active material of the dried negative electrode slurry.
[0117] Specifically, the rolling may be performed at a temperature close to room temperature, more specifically, at a temperature of 20°C to 35°C, 20°C to 30°C, or 20°C to 25°C.
[0118] The rolling may be performed at a rolling speed of 2 m / s to 7 m / s, more specifically, at a rolling speed of 2 m / s to 6.5 m / s, 2 m / s to 6 m / s, 2 m / s to 5.5 m / s, 2 m / s to 5 m / s, 2 m / s to 4.5 m / s, 2 m / s to 4 m / s, 2.5 m / s to 4 m / s, 2.5 m / s to 3.5 m / s, 3.5 m / s to 5 m / s, 5 m / s to 7 m / s, 5.5 m / s to 6.5 m / s, or 6 m / s to 7 m / s.
[0119] The rolling may be carried out under a pressure condition of 50 MPa to 200 MPa, specifically, under a pressure condition of 50 MPa to 150 MPa, 50 MPa to 100 MPa, 100 MPa to 200 MPa, 150 MPa to 200 MPa, or 80 MPa to 140 MPa.
[0120] The present invention can increase the energy density of the negative electrode while minimizing the change in the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer formed by rolling the dried negative electrode slurry under the above-mentioned temperature, speed and / or pressure conditions.
[0121] For example, the negative electrode active layer formed under the above conditions has a minimized change in the alignment degree of the carbon-based negative electrode active material, and the alignment degree (OI) of the carbon-based negative electrode active material after rolling is r ) may be 5 or less and may satisfy the following formula 2:
[0122] [Formula 2] 0.1≦[OI c ] / [OI r ]≦0.7
[0123] In the above formula 2, OI c represents the degree of alignment (OI) of the carbon-based negative electrode active material measured before rolling the negative electrode active layer, OI r represents the degree of alignment (OI) of the carbon-based negative electrode active material measured after rolling the negative electrode active layer, The degree of alignment (OI) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane and the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy analysis of the negative electrode active layer.
[0124] Specifically, the negative electrode active layer has an alignment degree (OI) of the carbon-based negative electrode active material after rolling. r ) may be 4.5 or less, 4.0 or less, 1.0 to 4.0, 2.0 to 4.0, 2.0 to 3.5, 2.0 to 3.0, 3.0 to 4.0, 3.0 to 3.5, 1.8 to 2.5, or 1.8 to 3.4.
[0125] In addition, the negative electrode active layer has an alignment degree ratio (OI) of the carbon-based negative electrode active material before and after rolling. c / OI r ) to 0.1 to 0.7 (i.e., 0.1 ≦ [OI c ] / [OI r]≦0.7), specifically, 0.1 to 0.65 (i.e., 0.1≦[OI c ] / [OI r ]≦0.65), 0.3~0.65 (i.e., 0.3≦[OI c ] / [OI r ]≦0.65), 0.4~0.65 (i.e., 0.4≦[OI c ] / [OI r ]≦0.65), 0.50~0.63 (i.e., 0.50≦[OI c ] / [OI r ]≦0.63), 0.45~0.55 (i.e., 0.45≦[OI c ] / [OI r ]≦0.55), or 0.55 to 0.65 (i.e., 0.55≦[OI c ] / [OI r ]≦0.65).
[0126] The method for producing a negative electrode for a lithium secondary battery according to the present invention has the above-mentioned configuration, and therefore can produce a negative electrode having excellent charge / discharge capacity and energy density, and having high charge characteristics and life characteristics during long-term charge / discharge of the secondary battery.
[0127] <Lithium secondary battery>
[0128] In one embodiment, the present invention further comprises: There is provided a lithium secondary battery including an electrode assembly including a positive electrode, the negative electrode according to the present invention described above, and a separator disposed between the positive electrode and the negative electrode.
[0129] The lithium secondary battery according to the present invention includes an electrode assembly having a structure in which a plurality of positive electrodes and a plurality of negative electrodes are alternately arranged with a separator disposed therebetween. The lithium secondary battery includes the above-described negative electrode according to the present invention, and has excellent charge / discharge capacity and energy density, and has excellent charge / discharge characteristics and life characteristics even during long-term charge / discharge, so that it can be usefully used as a power source for medium- to large-sized devices such as electric vehicles.
[0130] In this case, the negative electrode has the same configuration as that described above, and therefore a detailed description thereof will be omitted.
[0131] The positive electrode includes a positive electrode active layer including a positive electrode active material on a positive electrode current collector, and the positive electrode active layer may selectively further include a conductive material, a binder, other additives, and the like, as necessary.
[0132] The positive electrode active material is a material capable of electrochemically reacting on a positive electrode current collector, and may include at least one of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 capable of reversibly intercalating and deintercalating lithium ions:
[0133] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2
[0134] [Chemical formula 2] LiM 2 p Mn q P r O4
[0135] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつ、y+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is 0.05≦p≦1.0, q is 2-p, r is 0 or 1.
[0136] The lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 above are materials containing high amounts of nickel (Ni) and manganese (Mn), respectively, and when used as a positive electrode active material, have the advantage of being able to stably supply electricity with a high capacity and / or high voltage compared to conventionally commonly used positive electrode active materials such as iron phosphate oxide (LiFeO4).
[0137] In this case, the lithium metal oxide represented by the above chemical formula 1 is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.15 Al 0.05 O2, LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc., and the lithium metal oxide represented by the above chemical formula 2 is LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O 4、 LiNi 0.3 Mn 1.7 O4, etc., which may be used alone or in combination.
[0138] The positive electrode active material may be included in an amount of 85 parts by weight or more, specifically 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the weight of the positive electrode active layer.
[0139] The positive electrode active layer may further include a conductive material, a binder, and other additives in addition to the positive electrode active material.
[0140] In this case, the conductive material is used to improve the electrical performance of the positive electrode, and may be any conductive material commonly used in the art. Specifically, the conductive material may include at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.
[0141] The conductive material may be included in an amount of 0.1 to 5 parts by weight based on the weight of each positive electrode active layer, specifically 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.
[0142] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one or more resins selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As one example, the binder may include polyvinylidene fluoride.
[0143] The binder may be included in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, based on the weight of each positive electrode active layer.
[0144] The total thickness of the positive electrode active layer is not particularly limited, but may be specifically 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.
[0145] In addition, the positive electrode may use a positive electrode current collector having high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, those surface-treated with carbon, nickel, titanium, silver, etc. may also be used. In addition, the average thickness of the current collector may be suitably applied to be 3 μm to 500 μm, taking into consideration the conductivity and total thickness of the positive electrode to be manufactured.
[0146] In addition, the separator interposed between the positive and negative electrodes of each unit cell is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is one commonly used in the art, but specifically, one containing at least one polymer selected from polypropylene, polyethylene, and polyethylene-propylene copolymers having chemical resistance and hydrophobicity may be used. The separator may have a porous polymer substrate such as a sheet or nonwoven fabric containing the above-mentioned polymer, and may have a composite separator formed by coating organic or inorganic particles on the porous polymer substrate with an organic binder. The separator may have an average pore diameter of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.
[0147] Meanwhile, the lithium secondary battery according to the present invention is not particularly limited, and may be a secondary battery having a form that may include a stack type, a zigzag type, or a zigzag-stack type electrode assembly. As one example, the lithium secondary battery according to the present invention may be a pouch type secondary battery or a prismatic type secondary battery.
[0148] The pouch-type secondary battery and / or the prismatic secondary battery have the advantage that they can be highly utilized in terms of energy density since the secondary batteries can be packed at a high density in a limited space.
[0149] <Method of manufacturing lithium secondary battery>
[0150] Furthermore, in one embodiment, the present invention provides a method for producing the above-mentioned lithium secondary battery.
[0151] A method for manufacturing a lithium secondary battery according to the present invention includes the steps of inserting an electrode assembly including a positive electrode, a negative electrode of the present invention, and a separator disposed between the positive electrode and the negative electrode into a battery case, injecting a non-aqueous electrolyte solution, and then activating the assembled lithium secondary battery.
[0152] The activation step may refer to a process of electrically activating a lithium secondary battery and securing a path for lithium ions to move within the negative electrode active layer during charging and discharging.
[0153] Here, the present invention may be carried out under specific conditions to ensure a lithium ion migration path while minimizing damage and / or loss of the inclination of the ab-axis crystal plane of the carbon-based negative electrode active material contained in the negative electrode active layer relative to the negative electrode current collector during activation of the secondary battery.
[0154] Specifically, the activation step may involve charging and discharging two or more times under a constant current condition of less than 1 C rate. More specifically, the activation step may involve charging and discharging under a constant current condition of a C rate of 0.01 C to 0.9 C, 0.01 C to 0.75 C, 0.01 C to 0.5 C, 0.05 C to 0.5 C, or 0.05 C to 0.3 C. The activation step may involve charging and discharging two or more times, three or more times, four or more times, two to five times, or two to four times.
[0155] The present invention can secure a lithium ion migration path while minimizing the change in the degree of alignment of the ab-axis crystal plane of the carbon-based anode active material contained in the anode active layer by performing multiple charge and discharge cycles at a low current density of less than 1C during activation of the secondary battery. The lithium ion migration path thus secured can reduce the contraction and expansion of the carbon-based anode active material and the silicon-based anode active material during charge and discharge after activation. As a result, even if the lithium secondary battery of the present invention is charged and discharged for a long period of time, the change can maintain the high orientation of the ab-axis crystal plane of the carbon-based anode active material, and therefore it can exhibit excellent effects on charge and discharge characteristics and life characteristics.
[0156] The present invention will now be described in more detail with reference to examples and experimental examples.
[0157] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.
[0158] <Examples 1 to 3 and Comparative Examples 1 to 6. Production of Lithium Secondary Batteries>
[0159] <Production of negative electrodes>
[0160] Natural graphite (average particle size (D 50 ): 18±1μm) and artificial graphite (average particle size (D 50 ):16±1μm) and silicon oxide (SiO2) were prepared as a silicon-based negative electrode active material, and negative electrode slurries were produced using the prepared carbon-based negative electrode active material and silicon-based negative electrode active material.
[0161] Specifically, natural graphite and artificial graphite were mixed in a weight ratio of 15-25:75-85 to produce mixed graphite (average particle size (D 50A negative electrode active material was prepared by mixing 95 parts by weight of the prepared negative electrode active material, 1 part by weight of carbon black as a conductive material, 1.5 parts by weight of carboxymethyl cellulose (CMC) as a binder, and 2.5 parts by weight of styrene butadiene rubber (SBR) with water to a solid content of 50%.
[0162] After the negative electrode slurry was prepared, it was cast onto a copper sheet (thickness: 10 μm) that was being roll-to-roll transferred (transfer speed: 5 m / min) using a dual die coater. At this time, the loading amount of the applied negative electrode slurry was 208 to 210 mg / 25 cm. 2 It was.
[0163] Permanent magnets with a length ratio of 110~120% based on the width direction length of the negative electrode slurry were placed on the top of the applied negative electrode slurry and on the bottom of the negative electrode current collector, and a magnetic field was applied with a magnetic field strength of 4,700 G for the time shown in Table 1. The negative electrode slurry to which the magnetic field was applied was dried with hot air to form a negative electrode active layer on the negative electrode current collector in which the carbon-based negative electrode active material was oriented. The spectrum of the formed negative electrode active layer was measured by X-ray diffraction (XRD) spectroscopy analysis. The X-ray diffraction measurement conditions were as follows:
[0164] - Target: Cu (Kα line) graphite monochromator -Slit: Divergence slit = 1 degree, Receiving slit = 0.1mm, Scattering slit = 1 degree -Measurement area: (1,1,0) plane: 76.5 degrees < 2θ < 78.5 degrees / (0,0,4) plane: 53.5 degrees < 2θ < 56.0 degrees
[0165] The formed negative electrode active layer was then rolled at 22±1° C. under a pressure of 100 MPa to 150 MPa and a transfer speed of 3 m / s to prepare a negative electrode for a lithium secondary battery (average thickness of the negative electrode active layer before rolling: 87 to 88 μm / average thickness after rolling: 58 to 66 μm). X-ray diffraction (XRD) spectroscopy was additionally performed on the rolled negative electrode active layer to measure the spectrum.
[0166] The degree of alignment (OI) of the mixed graphite was calculated from the spectra measured before and after rolling using the following formula 3, and the results are shown in Table 1 below.
[0167] [Formula 3] OI=I 004 / I 110
[0168] In Equation 3, I 004 represents the area of the peak showing the (0,0,4) crystal plane of the carbon-based negative electrode active material in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer, I 110 represents the area of the peak showing the (1,1,0) crystal plane of the carbon-based negative electrode active material in X-ray diffraction (XRD) spectroscopic analysis of the negative electrode active layer.
[0169] [Table 1]
[0170] <Production of positive electrodes>
[0171] The positive electrode active material is LiNi with a particle size of 5 μm. 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 was prepared and mixed with polyvinylidene fluoride as a carbon-based conductive material and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a positive electrode slurry, which was then applied to an aluminum sheet. The aluminum sheet to which the positive electrode slurry was applied was then dried in a vacuum oven at 120°C and rolled to produce a positive electrode (average thickness of the positive electrode active layer: 100±10μm).
[0172] <Manufacturing lithium secondary batteries>
[0173] An electrode assembly was prepared by interposing a separator made of polypropylene having a thickness of 18 μm between the obtained positive electrode and the negative electrode prepared in each of Examples 1 to 3 and Comparative Examples 1 to 6. The prepared electrode assembly was inserted into a case, and a non-aqueous electrolyte composition was injected into the case to assemble a lithium secondary battery.
[0174] The assembled lithium secondary battery was activated at 22±1° C. to manufacture a lithium secondary battery. The activation was performed under a constant current condition with a current density shown in Table 2 below.
[0175] The negative electrode was disassembled from each activated lithium secondary battery, and the negative electrode active layer was subjected to X-ray diffraction (XRD) spectroscopy analysis. The XRD conditions were the same as those used previously. The degree of alignment (OI) of the mixed graphite was determined from the measured XRD spectrum. a The degree of alignment of the carbon-based negative electrode active material (OI) of the activated negative electrode was calculated. a ) and the degree of alignment of the carbon-based negative electrode active material before activation (OI r The results are shown in Table 2 below.
[0176] [Table 2]
[0177] <Experimental Example>
[0178] In order to confirm the performance of the negative electrode according to the present invention, the initial charge / discharge capacity and life characteristics were evaluated for the lithium secondary batteries produced in Examples 1 to 3 and Comparative Examples 1 to 6.
[0179] Specifically, each lithium secondary battery activated in Examples 1 to 3 and Comparative Examples 1 to 6 was charged and discharged once. At this time, the charging was performed at a constant current (CC) of 1.0 C at a temperature of 25° C. until the voltage reached 5 mV, and then at a constant voltage (CV) until the charging current reached 0.005 C (cut-off current). The discharging was performed at a constant current (CC) of 1.0 C at a temperature of 25° C. until the voltage reached 1.5 V, after leaving the battery for 20 minutes after charging. The capacity of each lithium secondary battery during charging and discharging was measured, and the measured charging capacity and discharging capacity were determined to be the initial charging and discharging capacity of each lithium secondary battery. The results are shown in Table 3 below.
[0180] Each lithium secondary battery whose initial charge / discharge capacity had been measured was charged / discharged 299 times under the same conditions. After the 299th charge / discharge, the charge and discharge capacities of each lithium secondary battery were measured. The measured charge and discharge capacities were determined to be the 300th charge / discharge capacity of each lithium secondary battery, and the capacity retention rate was calculated based on the initial charge / discharge capacity. The results are shown in Table 3 below.
[0181] [Table 3]
[0182] As shown in Table 3, it is apparent that the negative electrode according to the present invention has excellent charge / discharge capacity and life characteristics.
[0183] Specifically, the lithium secondary battery of the embodiment has: (1) the degree of alignment (OI) of the carbon-based negative electrode active material after activation; a ) is adjusted to 3 or less, and (2) the degree of alignment (OI) of the carbon-based negative electrode active material before and after activation is adjusted a / OI r ) is controlled to be 0.5 or more and less than 1. As a result, it was shown that the above-mentioned lithium secondary battery has a charge capacity and a discharge capacity at the initial charge / discharge of 461 mAh / g or more and 398 mAh / g or more, respectively, and a capacity retention rate after 300 charge / discharge cycles of 87% or more.
[0184] On the other hand, the lithium secondary batteries of the comparative examples did not include all of the above components, and although their initial charge / discharge capacities were lower or equivalent to those of the examples, it was confirmed that their capacity retention rates after 300 charge / discharge cycles were significantly low.
[0185] This indicates that the negative electrode of the embodiment contains both a carbon-based negative electrode active material and a silicon-based negative electrode active material, and has high charge / discharge capacity and energy density. In addition, the negative electrode firmly secures a lithium ion migration path in the negative electrode active layer during activation, which means that even when the secondary battery is charged and discharged for a long period of time, the contraction and expansion of the negative electrode active material due to the insertion and extraction of lithium ions is suppressed, and damage and / or loss of the degree of alignment (OI) of the carbon-based negative electrode active material is minimized.
[0186] From these results, it is apparent that the negative electrode for a lithium secondary battery according to the present invention is excellent in charge characteristics and life characteristics during long-term charge and discharge.
[0187] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art may make various modifications and changes to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.
[0188] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but is defined by the claims.
Claims
1. A negative electrode current collector, and a negative electrode active layer provided on at least one surface of the negative electrode current collector and including a carbon-based negative electrode active material and a silicon-based negative electrode active material; The negative electrode active layer is The degree of alignment of the carbon-based negative electrode active material after activation (O.I. a ) is 3 or less, A negative electrode for a secondary battery that satisfies the following formula 1: [Formula 1] 0.5≦[O.I] a ] / [O.I r ]<1.0 In the above formula 1, O.I. r represents the degree of alignment (O.I) of the carbon-based negative electrode active material measured before activation, O.I. a represents the degree of alignment (O.I) of the carbon-based negative electrode active material measured after activation, The degree of alignment (O.I) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane to the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy of the negative electrode active layer.
2. The average particle size (Dc) of the carbon-based negative electrode active material is 5 μm to 50 μm; The average particle size (Ds) of the silicon-based negative electrode active material is 0.5 μm to 10 μm, and 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the ratio (Dc / Ds) of average particle diameters of the carbon-based negative electrode active material and the silicon-based negative electrode active material is 1 to 10.
3. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based negative electrode active material is contained in an amount of 1% by weight to 20% by weight based on the total weight of the negative electrode active material.
4. The negative electrode for a lithium secondary battery according to claim 1 , wherein the carbon-based negative electrode active material comprises at least one of natural graphite and artificial graphite.
5. The silicon-based negative electrode active material is silicon (Si), silicon carbide (SiC) and silicon oxide (SiO q 2. The negative electrode for a lithium secondary battery according to claim 1, comprising at least one of the following:
6. The negative electrode active layer has a thickness of 150 mg / 25 cm 2 ~300mg / 25cm 2 The negative electrode for a lithium secondary battery according to claim 1 , having a loading amount of
7. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the negative electrode active layer has an average thickness of 10 μm to 100 μm.
8. applying a negative electrode slurry containing a carbon-based negative electrode active material and a silicon-based negative electrode active material to at least one surface of a negative electrode current collector; applying a magnetic field to the applied negative electrode slurry; drying and rolling the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; The negative electrode active layer is The degree of alignment of the carbon-based negative electrode active material after activation (O.I. a ) is 3 or less, A method for producing a negative electrode for a lithium secondary battery according to any one of claims 1 to 7, which satisfies the following formula 1: [Formula 1] 0.5≦[O.I] a ] / [O.I r ]<1.0 In the above formula 1, O.I. r represents the degree of alignment (O.I) of the carbon-based negative electrode active material measured before activation, O.I. a represents the degree of alignment (O.I) of the carbon-based negative electrode active material measured after activation, The degree of alignment (O.I) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane to the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy of the negative electrode active layer.
9. The method for producing a negative electrode for a lithium secondary battery according to claim 8, wherein the step of applying a magnetic field is performed at a magnetic field strength of 3,000 G to 9,000 G.
10. The method for producing a negative electrode for a lithium secondary battery according to claim 8, wherein the step of applying the magnetic field is performed for 1 second to 30 seconds.
11. The method for producing a negative electrode for a lithium secondary battery according to claim 8, wherein the rolling is carried out at a temperature of 20° C. to 35° C. and a pressure of 50 MPa to 200 MPa.
12. A lithium secondary battery comprising an electrode assembly comprising a positive electrode, the negative electrode according to claim 1, and a separator disposed between the positive electrode and the negative electrode.
13. The lithium secondary battery according to claim 12, wherein the positive electrode is provided on at least one surface of a positive electrode current collector and includes at least one positive electrode active material selected from lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2: [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O 2 [Chemical formula 2] LiM 2 p Mn 1-p O 4 In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more elements selected from the group consisting of W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are each within the range of 1.0≦x≦1.30, 0.5≦y<1, 0<z≦0.3, 0<w≦0.3, 0≦v≦0.1, and y+z+w+v=1; M 2 is Ni, Co or Fe, p is in the range of 0.05≦p≦1.
0.
14. activating a lithium secondary battery including an electrode assembly including a positive electrode, the negative electrode according to claim 1, and a separator disposed between the positive electrode and the negative electrode; The negative electrode active layer of the negative electrode is The degree of alignment of the carbon-based negative electrode active material after activation (O.I. a ) is 3 or less, A method for producing a lithium secondary battery that satisfies the following formula 1: [Formula 1] 0.5≦[O.I] a ] / [O.I r ]<1.0 In the above formula 1, O.I. r represents the degree of alignment (O.I) of the carbon-based negative electrode active material measured before activation, O.I. a represents the degree of alignment (O.I) of the carbon-based negative electrode active material measured after activation, The degree of alignment (O.I) represents the ratio of the area integral value of the peak at 2θ=54.7±0.2° representing the (0,0,4) plane to the peak at 2θ=77.5±0.2° representing the (1,1,0) plane in X-ray diffraction spectroscopy of the negative electrode active layer.
15. The method for producing a lithium secondary battery according to claim 14, wherein the activation step is performed by charging and discharging the battery at a rate of 0.01 C to 0.9 C at least twice.
Citation Information
Patent Citations
Negative electrode for rechargeable lithium battery, and rechargeable lithium battery including same
EP3561914A1
Nonaqueous electrolyte secondary battery
JP2014086258A
Negative electrode for secondary battery
JP2018129212A
Anode for lithium ion secondary battery, method for preparing the same, and lithium ion secondary battery comprising the same
JP2022074139A
Negative electrode for lithium secondary battery and lithium secondary battery including the same
JP2022167890A